1997
DOI: 10.1677/joe.0.1520447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone on cholesterol metabolism in the lactating rat mammary gland

Abstract: Lactating rats were treated for 48 h with bromocriptine (to inhibit prolactin release) or bromocriptine together with an antiserum to rat GH. Animals given the combined treatment were also supplemented concurrently with bovine GH (bGH) or human insulin-like growth factor-I (hIGF-I). The effects of these treatments on the activities of 3-methyl-3-glutaryl-CoA reductase (HMG-CoA reductase), acyl-CoA:cholesterol acyltransferase (ACAT) and neutral cholesteryl ester hydrolase (CEH) and on the microsomal concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…We have previously demonstrated that PRL and GH play supporting roles in various aspects of mammary gland function, including established milk synthesis (25), casein synthesis (26), lipid synthesis (27,28), and mammary cholesterol metabolism (29), although the role of PRL was always quantitatively dominant. Subsequently, we offered a mechanistic explanation for this interaction when we described their interactive roles in maintaining epithelial cell survival (27,30,31) and controlling mammary plasminogen activation to plasmin.…”
mentioning
confidence: 99%
“…We have previously demonstrated that PRL and GH play supporting roles in various aspects of mammary gland function, including established milk synthesis (25), casein synthesis (26), lipid synthesis (27,28), and mammary cholesterol metabolism (29), although the role of PRL was always quantitatively dominant. Subsequently, we offered a mechanistic explanation for this interaction when we described their interactive roles in maintaining epithelial cell survival (27,30,31) and controlling mammary plasminogen activation to plasmin.…”
mentioning
confidence: 99%